Austenite carbon enrichment and decomposition during quenching and tempering of high silicon high carbon bearing steel. (1st April 2023) - Ribamar, G.G.; Escobar, J.D.; Kwiatkowski da Silva, A.; Schell, N.; Ávila, J.A.; Nishikawa, A.S.; Oliveira, J.P.; Goldenstein, H.
Abstract: The addition of Si to steels is a well stablished method to delay cementite precipitation, allowing for carbon partitioning from martensite to retained austenite during tempering. It has been argued that carbon enrichment and stabilization of austenite leads to increased ductility and toughness. This has been the main motivation for the development of novel heat treatments, such as quenching and partitioning. High carbon steels can also benefit from improved ductility provided by the presence of stabilized retained austenite. However, the process of carbon partitioning is less understood due to the increased tendency for competitive carbide formation with increasing carbon content. The present work investigates the austenite carbon partitioning and austenite decomposition phenomena in a modified 1.82 wt.% Si hypereutectoid bearing steel during tempering. Dilatometry, in-situ and ex-situ synchrotron X-ray diffraction, 3D atom probe tomography, scanning electron microscopy, and hardness measurements were used. The results are discussed based on different equilibrium states between α' and carbides. It was found that carbon partitioning towards retained austenite occurs for several minutes without significant phase decomposition at temperatures lower than 300 °C. A transition temperature between prevalent austenite carbon enrichment and austenite decomposition occurs at 350 °C. Secondary cementite precipitation inside martensite, and at the α'/γ interfaces, is observed during tempering at temperatures above 400 °C. Results from constrained carbon equilibrium modeling with carbide presence indicate that homogeneously dispersed spheroidized primary cementite has little influence in the carbon partitioning phenomenon. Graphical abstract: Figure i – Main tempering phenomena occurring during tempering between 200 and 500 °C: Heat cycles, carbon distribution via APT measurement, microhardness, austenite volume fraction, austenite carbon content and SEM after tempering at different temperatures. Image, graphical abstract